Prediction of pregnancy success rate through in vitro fertilization based on maternal age (Medical Journal of Indonesia, 2009)
Aim To evaluate the correlation between the success of pregnancy through in vitro fertilization and maternal age. Methods Assessment of pregnancy was performed in eight in vitro fertilization centers in Indonesia: Harapan Kita Pediatric and Obstetric Hospital from 1997 to 2001, and seven in vitro fertilization centers in Indonesia. Follicular induction was performed through the long protocol, short protocol and natural cycle. Insemination was performed through ICSI (intra cytoplasmic sperm injection) on petri dish. Spermatozoa were obtained through masturbation, testicular biopsy and epididimical biopsy. A successful pregnancy was indicated chemically, with the presence of fetal heart beat and the birth of a baby (take home baby). Results There was a 34% pregnancy rate for the age group below 30 years, 33.75% for those between 31 and 35 years olds, and 26% for the age group 36 to 40 years old, and 8% for the age group above 40 years. Conclusion The higher the maternal age, the lower pregnancy rate. In other words, the higher the maternal age, the higher the rate of miscarriage. (Med J Indones 2009; 18: 244-8)